2018
DOI: 10.14740/jocmr3465w
|View full text |Cite
|
Sign up to set email alerts
|

Ear Involvement in Inflammatory Bowel Disease: A Review of the Literature

Abstract: Inflammatory bowel disease (IBD) is a multisystemic disease. The ear is a rare but recognized site of extraintestinal manifestations of IBD. In external ear, the more common manifestations of IBD are pyoderma gangrenosum, metastatic Crohn’s disease and relapsing polychondritis and the treatment includes corticosteroids and anti-TNF agents. Sensorineural hearing loss (SNHL) is the most common ear disease in IBD and especially in patients with ulcerative colitis. In most cases of IBD patients with SNHL, the hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, in our patient, vestibular neuronitis was accompanied by a very moderate and transient increase in blood CRP at the time of the AE occurrence. It is interesting to notice that the ear is a rare but recognized site of extra-intestinal manifestations of IBD [17]. The etiology of vestibular neuronitis disease remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our patient, vestibular neuronitis was accompanied by a very moderate and transient increase in blood CRP at the time of the AE occurrence. It is interesting to notice that the ear is a rare but recognized site of extra-intestinal manifestations of IBD [17]. The etiology of vestibular neuronitis disease remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As both RP and IBD are immune-mediated diseases, they can theoretically appear together. Reportedly, RP has been introduced as one of the extra-intestinal manifestations (EIMs) of IBD, but compared to other EIMs, such as peripheral and axial arthropathies, erythema nodosum, and pyoderma gangrenosum, RP is an extremely rare EIM of IBD [ 8 , 9 ]. Furthermore, RP is easily overlooked by clinicians, owing to its non-specific and unusual manifestations [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fousekis et al suggested initial corticosteroid therapy for SNHL, if that fails anti TNF agents and the last resort being cochlear implantation. 11 Kanzaki and O-uchi et al suggested that adequate treatment of Primary IBD causes improvement of SNHL. 9 The present study emphasises the importance of early identification of SNHL in patients of IBD through periodic testing of pure tone thresholds before severe hearing impairment occurs.…”
Section: Discussionmentioning
confidence: 99%
“…10 SNHL due to autoimmune disease is usually diagnosed based on clinical presentation. 11 Otoscopic examination, tympanometry and pure tone audiometry help in assessing the level of hearing loss. The response to treatment can also be monitored by serial audiometric testing at regular intervals.…”
mentioning
confidence: 99%